The Fund's Income Position for FY 2011 : Midyear Review. (Policy Papers; Policy Paper, 2010)
This paper updates the outlook for the IMF's income position for the financial year 2011 taking into account developments in the first half of the year. The outlook has improved primarily reflecting additional lending activity, which raised the projected average credit outstanding in FY 2011 by about SDR 3 billion to SDR 54 billion. Net operational income for FY 2011 is projected at SDR 328 million, some SDR 126 million higher than the projection in April 2010.1 The actual outcome is subject to considerable uncertainty related to the timing and amounts of disbursements under current and potential new arrangements and the performance of the Investment Account (IA).